2021
DOI: 10.1136/tsaco-2020-000660
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal deployment strategy for REBOA in patients with non-compressible hemorrhage below the diaphragm

Abstract: BackgroundNon-compressible truncal hemorrhage (NCTH) is the leading cause of preventable death after trauma. Resuscitative endovascular balloon occlusion of the aorta (REBOA) achieves temporary hemorrhage control, supporting cardiac and cerebral perfusion prior to definitive hemostasis. Aortic zone selection algorithms vary among institutions. We evaluated the efficacy of an algorithm for REBOA use.MethodsA multicenter prospective, observational study conducted at six level 1 trauma centers over 12 months. Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…27 In addition, the Emergent Truncal Hemorrhage Control study investigators evaluated a commonly accepted REBOA algorithm to determine adherence to optimal zone placement, 28 and the investigators found that, of the 36 Zone 1 REBOAs placed, 4 (11.1%) should have been Zone 3 and, of those patients, 3 ultimately died because of MOF. 29 To our knowledge, our swine experiment is the first to comprehensively characterize the significant coagulopathic disparities between Zone 1 and Zone 3 occlusion. Compared with AO Zone 3, Zone 1 was associated with significant TEG-measured coagulation abnormalities, including prolonged time to clot formation, poor clot strength, and increased occult fibrinolysis.…”
Section: Discussionmentioning
confidence: 96%
“…27 In addition, the Emergent Truncal Hemorrhage Control study investigators evaluated a commonly accepted REBOA algorithm to determine adherence to optimal zone placement, 28 and the investigators found that, of the 36 Zone 1 REBOAs placed, 4 (11.1%) should have been Zone 3 and, of those patients, 3 ultimately died because of MOF. 29 To our knowledge, our swine experiment is the first to comprehensively characterize the significant coagulopathic disparities between Zone 1 and Zone 3 occlusion. Compared with AO Zone 3, Zone 1 was associated with significant TEG-measured coagulation abnormalities, including prolonged time to clot formation, poor clot strength, and increased occult fibrinolysis.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, abdominal ultrasound can be used for procedural guidance. For example, studies demonstrate its usefulness in ensuring proper Foley catheter placement, intrauterine placement of catheters to tamponade hemorrhage, and as part of an algorithm to ensure appropriate placement of resuscitative endovascular balloon occlusion of the aorta (REBOA) devices following trauma 50–52. See Table 1 for a summary of the indications for the FAST exam in the trauma, critical care, and perioperative setting.…”
Section: Fast Indicationsmentioning
confidence: 99%
“…multiple organ dysfunction principi lečenja preloma karlice kod politraumatizovanih pacijenata principles of pelvic fracture treatment in polytrauma patients to ischemia-reperfusion injury. This problem is prevented by applying short REBOA, intermittent REBOA (iREBOA), Zone 3 REBOA, and partial REBOA [22,23].…”
Section: Reanimacijska Endovaskularna Balonska Okluzija Aorte (Reboa)mentioning
confidence: 99%
“…syndrome -MODS) usled ishemijsko -reperfuzijske reakcije. Ovaj problem se prevenira kratkotrajnom REBOA procedurom, intermitentnom REBOA procedurom (iREBOA), Zona 3 REBOA procedurom i parcijalnom REBOA procedurom [22,23].…”
Section: Dco As a Part Of Dcrunclassified